Visualising the Titanic disaster. Issue 1 (6th February 2019) - Friendly, Michael; Symanzik, Jürgen; Onder, Ortac
Abstract : The sinking of the Titanic has inspired books, movies and documentaries. But it has also motivated data visualisation designers to tell the story of the tragedy in new ways.Michael Friendly, Jürgen Symanzik andOrtac Onder review the first graph of the disaster and some recent history Abstract : The sinking of the Titanic has inspired books, movies and documentaries. But it has also motivated data visualisation designers to tell the story of the tragedy in new ways. Michael Friendly, Jürgen Symanzik and Ortac Onder review the first graph of the disaster and some recent history.